Land Proprietary Rights and Limitations in Private and Public Interests - NIYAZOVA, Anara N.; SULEIMENOV, Maidan K.; ILYASSOVA, Kulyash M.; KAZIYEVA, Gulzhaukhar T.; SARINA, Salima A. (Journal of Advanced Research in Law and Economics, 2016)
The article considers the actual issues of the institution and the subjective land proprietary right development. The content of land proprietary right is analyzed in terms of immanent inherent limitations and obligations. The methodological basis of the study is a set of methods of scientific knowledge, among which the leading place a general scientific method of deduction and private-scientific research methods – functional analysis and modeling. The article states not only economic domination over a thing, but also limits of powers constitute the content of land proprietary right. The legislator in view of specificity involved in the civil land turnover, which are projecting natural objects at the same time, established mandatory requirements for the subject composition and terms of the subjective rights. Being exhausted, nonrenewable natural sites, land belonging to the territory of the State, should be preserved for present and future generations. This explains the position of the legislator in the regulation of considered relations in private and public interests. The implementation of land proprietary right is associated with the observance of both the private and public interests that require harmonization in order to avoid conflicts.